2002
DOI: 10.1046/j.0022-202x.2001.01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Water Barrier Function in Epidermal-Type Fatty Acid Binding Protein-Deficient Mice

Abstract: We have generated mutant mice for epidermal-type fatty acid binding protein by the gene targeting technique and examined the phenotype in detail. Despite a lack in the expression of epidermal-type fatty acid binding protein mRNA and its protein in the skin and other tissues of the mutant mice, the animals appeared normal in gross and histologic examination. Northern blot analysis of other fatty acid binding proteins revealed a distinct elevated gene expression of heart-type fatty acid binding protein in the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 46 publications
2
53
0
1
Order By: Relevance
“…The amount of E-FABP increases with keratinocyte differentiation, and immunohistochemistry studies have demonstrated that the intensity of staining is greatest in the upper epidermis (96,98,99). The expression of brain, liver, and heart FABP is not usually detected in the epidermis (100,101). Acute disruption of the permeability barrier induces E-FABP expression, and this increase can be prevented by covering with a vapor-permeable membrane (102).…”
Section: Jlr: Are There Fatty Acid Binding Proteins In Keratinocytes?mentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of E-FABP increases with keratinocyte differentiation, and immunohistochemistry studies have demonstrated that the intensity of staining is greatest in the upper epidermis (96,98,99). The expression of brain, liver, and heart FABP is not usually detected in the epidermis (100,101). Acute disruption of the permeability barrier induces E-FABP expression, and this increase can be prevented by covering with a vapor-permeable membrane (102).…”
Section: Jlr: Are There Fatty Acid Binding Proteins In Keratinocytes?mentioning
confidence: 99%
“…Additionally, inflammatory disorders, including psoriasis, are associated with increased E-FABP levels in the epidermis (95,97,98). In animals deficient in E-FABP, basal transepidermal water loss is lower than in wild-type animals, (100,101). Of note, though, is that heart FABP is expressed in the epidermis of E-FABP knockout mice (usually not detectable in wild-type mice), and it is possible that this increase in heart FABP compensates for the absence of E-FABP (100, 101).…”
Section: Jlr: Are There Fatty Acid Binding Proteins In Keratinocytes?mentioning
confidence: 99%
“…However, E-FABP-null mice generated by us are viable, and neither macro-nor microscopic abnormalities have been detected in the brain (Owada et al 2002b). Further studies are necessary to clarify the physiological function of E-FABP in the brain.…”
Section: E-fabp (Fabp5)mentioning
confidence: 99%
“…At least 12 members of a genetically related family have been identified, which display distinct patterns of tissue distribution (7). Among the FABP family proteins, FABP5 is expressed in human and murine epidermis and sebaceous glands (8)(9)(10). In the epidermis, FABP5 expression is increased with keratinocyte differentiation, and highly expressed in stratum granulosum where lipid synthesis is active in intercellular lipid production (9-11).…”
Section: Accepted For Publication 25 April 2012mentioning
confidence: 99%
“…The generation of FABP5-deficient mice has been described previously (10). Sebaceous glands morphology, immunohistochemical staining and sebaceous lipid composition were evaluated using wild-type and FABP5-deficient mice.…”
Section: Experimental Designmentioning
confidence: 99%